2015
DOI: 10.1902/jop.2014.140259
|View full text |Cite
|
Sign up to set email alerts
|

Meloxicam Temporally Inhibits the Expression of Vascular Endothelial Growth Factor Receptor (VEGFR)‐1 and VEGFR‐2 During Alveolar Bone Repair in Rats

Abstract: In rat alveolar bone repair, meloxicam did not affect VEGF expression but downregulated VEGFR expression, which may cause a delay in the bone repair/remodeling process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
(94 reference statements)
1
6
0
Order By: Relevance
“…The histomorphometric analysis confirms the μCT data, depicting the initial bone formation at the 7d time period, and the gradual increase in the bone mass until the alveolar socket was totally filled by newly formed bone at 21d. Accordingly, a similar kinetics of bone neoformation was previously described in a rat model [ 3 , 5 , 77 ]. The molecular data support the histomorphometric evidences of progressive bone healing at the 14d time period, since markers of advanced osteoblastic differentiation and osteocyte markers, such as PHEX (phosphate-regulating neutral endopeptidase), DMP1 (dentin matrix protein 1) and SOST (sclerostin)[ 78 , 79 ], are upregulated at this time period.…”
Section: Discussionmentioning
confidence: 87%
“…The histomorphometric analysis confirms the μCT data, depicting the initial bone formation at the 7d time period, and the gradual increase in the bone mass until the alveolar socket was totally filled by newly formed bone at 21d. Accordingly, a similar kinetics of bone neoformation was previously described in a rat model [ 3 , 5 , 77 ]. The molecular data support the histomorphometric evidences of progressive bone healing at the 14d time period, since markers of advanced osteoblastic differentiation and osteocyte markers, such as PHEX (phosphate-regulating neutral endopeptidase), DMP1 (dentin matrix protein 1) and SOST (sclerostin)[ 78 , 79 ], are upregulated at this time period.…”
Section: Discussionmentioning
confidence: 87%
“… 34 Animal studies have confirmed that the temporary inhibition of VEGFR-1 and VEGFR-2 expression by meloxicam correlated with the time of its administration, but no difference was found in VEGF expression compared to the control group. 35 …”
Section: Nsaids and Angiogenesismentioning
confidence: 99%
“…VEGFR-2 contains 19 tyrosine residues. [22] The extent to which the multitude of tyrosines in its cytoplasmic tail is differentially phosphorylated remains unclear. The binding mechanism of different SH2 domain-containing proteins, which leads to activation of gene induction patterns and receptor-specific intracellular signaling, is also unclear.…”
Section: Effect Of Vascular Endothelial Growth Factor On Endothelial mentioning
confidence: 99%